Age should be considered in cut-off values for increased carotid intima-media thickness - Ayşe Selcan Koç; Hilmi Erdem Sümbül (KARE Publishing, 2019)
Objective: The current guidelines use a cut-off value of 0.9 mm to define abnormally increased carotid intima-media thickness (C-IMT), regardless of age or gender. This study was conducted to examine the effects of age and gender on C-IMT and cut-off values for C-IMT in different age groups. Methods: A total of 644 patients with a recorded C-IMT measurement, at least 1 cardiovascular risk factor, and aged between 20 and 90 years were included in the study. Common and internal C-IMT (CC-IMT and IC-IMT) measurements were obtained using carotid ultrasonography (USG). The patients were divided into 5 groups based on age: Group I (20-40 years), Group II (41-50 years), Group III (51-60 years), Group IV (61-70 years), and Group V (>70 years). Results: The CC-IMT and IC-IMT values were significantly greater as the age of the group increased. Group I to Group V had a median CC-IMT value of 0.70 mm, 0.70 mm, 0.75 mm, 0.75 mm, and 0.85 mm, respectively. The median IC-IMT value for each group was 0.60 mm, 0.65 mm, 0.70 mm, 0.70 mm, and 0.80 mm, respectively. The median CC-IMT value was 50 μm greater than the median IC-IMT value in all groups. Only the CC-IMT value was significantly different in males (0.80+-0.20 mm vs. 0.76+-0.19 mm; p=0.020). Age, hypertension (HT), smoking, hyperlipidemia, systolic-diastolic blood pressure, and body mass index measures were associated with increased C-IMT. Regression analysis revealed that increased C-IMT was independently associated with age and HT presence. Each decade of life and the presence of HT revealed an incidence of increased C-IMT by 44% and 53%, respectively. Conclusion: C-IMT significantly increased with age. New, age-appropriate cut-off values are needed for C-IMT assessment. In addition, it was observed that the CC-IMT value was approximately 50 μm greater than the IC-IMT measurement in all age groups. CC-IMT measurements should be included in USG reports.